Intracerebral hemorrhage associated with brucellosis: A case report - Luo, Yusong; Tian, Guopeng; Lin, Maoqiang; Fang, Xiang; Bai, Shengwei; Pan, Yawen (Frontiers in Neurology, 2022)
Background：Intracerebral hemorrhage is a common disease, but cases of intracerebral hemorrhage with brucellosis are very rare. Here, we are presenting a case of a 60-year-old male patient diagnosed with brucellosis who has a right basal ganglia hemorrhage ruptured into bilateral lateral ventricles. Case presentation：A 60-year-old male patient with symptoms of intracerebral hemorrhage who had no common risk factors for intracerebral hemorrhage, but having been diagnosed with brucellosis 2 months earlier and telling a shepherd history for 3 years. Cranial computed tomography (CT) and cranial magnetic resonance angiography (MRA) revealed that an intracerebral hemorrhage in the right basal ganglia had broken into bilateral lateral ventricles, and a Brucella serology test was positive. The patient's condition improved significantly after receiving bilateral lateral ventricle cone drainage, hematoma cavity cone drainage and anti-brucellosis treatment. Conclusions：Herein, we discuss the possible mechanisms and clinical implications between brucellosis and intracerebral hemorrhage. This case suggests whether we can use brucellosis as a routine examination for disease diagnosis and prevention in patients with intracerebral hemorrhage from pastoral areas.